Learning facilities and infrastructure based on the characteristics of Children with Special Needs in inclusive education - Azzahra, Indah Maysela; Diana, Raden Rachmy; Nirwana, Evi Selva; Wiranata, Rz. Ricky Satria; Andriani, Kiki Melita (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2022)
The need for learning facilities and infrastructure in inclusive PAUD (Early Childhood Education) is still limited. This study aims to contribute to every manager of inclusive and regular PAUD institutions in providing learning infrastructure needs for all students based on applicable standards or provisions. The research method uses a qualitative method of literature study. Miles and Huberman's interactive analysis carried out the data analysis technique, which consisted of data collection, reduction, presentation, and conclusion. Data was collected from reading references such as articles, books, and inclusive PAUD POS issued by the Indonesian Ministry of Education and Culture. The study's results found that each characteristic of children with special needs has different needs for facilities and infrastructure. In addition, it was found that several infrastructure facilities could be designated for other different types of children with special needs characteristics, such as rooms, equipment, media, and student learning resources. The conclusion is that inclusive PAUD institutions need to provide modified infrastructure based on each characteristic of children with special needs so that they can be used inclusively.